2022
DOI: 10.1111/iwj.14015
|View full text |Cite
|
Sign up to set email alerts
|

The effect of liposomal bupivacaine for surgical wound infiltration: A meta‐analysis of randomised controlled trials

Abstract: Liposomal bupivacaine (LB) has consistently been considered a potential analgesic for surgical wound infiltration. However, the evidence of its analgesic effectiveness remains unclear. In this meta‐analysis, we attempted to identify the potential clinical role of LB wound infiltration in different surgical procedures. Randomised controlled trials (RCTs) comparing LB with non‐liposomal local anaesthetics and placebos were retrieved from six electronic databases. The primary outcome was cumulative morphine equiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…[35][36][37][38] Liposomal bupivacaine, as investigated in the current study, was initially used for surgical infiltration with the main focus on postoperative pain therapy. [11][12][13]24,25,29 Only then was the spectrum of applications expanded to interscalene brachial plexus, 15,16 femoral nerve, 18,39 intercostal nerve, [19][20][21][22][23]40 and fascial plane block 41 techniques.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[35][36][37][38] Liposomal bupivacaine, as investigated in the current study, was initially used for surgical infiltration with the main focus on postoperative pain therapy. [11][12][13]24,25,29 Only then was the spectrum of applications expanded to interscalene brachial plexus, 15,16 femoral nerve, 18,39 intercostal nerve, [19][20][21][22][23]40 and fascial plane block 41 techniques.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the available research has dealt with infiltration and fascial plane techniques, which cannot truly be considered regional anesthesia. 12,13,24,25 Those very few studies in the literature that do report on liposomal bupivacaine for peripheral nerve blockade have recently been subjected to meta-analysis, the results of which have engendered great controversy. 26 Despite a good base of citable reports, little is known about the pharmacodynamic characteristics of liposomal bupivacaine, considering that the available clinical studies almost invariably used postoperative opioid requirements as their primary outcome measure.…”
Section: Liposomal Bupivacaine For Nerve Blockadementioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis is a powerful tool that can combine the results of two or more individual studies, demonstrates a good evidence advantage, and contributes to healthcare decision making ( Mohd-Ali and Chen, 2021 ; Ozek et al, 2021 ). Jiang et al (2023) conducted a meta-analysis and reported the effect of bupivacaine on the postoperative analgesic, rehabilitation, and safety outcomes for surgical wound infiltration. However, there is no meta-analysis reporting the analgesic effect and safety of bupivacaine in patients undergoing hemorrhoidectomy.…”
Section: Introductionmentioning
confidence: 99%